Analysis of changes in mangrove cover during 2005-2018 using LANDSAT Satellite Imagery in Pangandaran District - Syamsuddin, Mega Laksmini; Shinta, Shinta; Andriani, Yuli; Subiyanto, Subiyanto (Universitas Malikussaleh, 2025)
A high-based information system using a remote sensing system through satellite imagery can be used as an alternative to mapping the distribution of mangroves by using satellite technology. This research was conducted in Pangandaran district, including 3 locations, e.g., Nusa Wiru, Bojong Salawe, and Karang Tirta Mangrove Forests. The purpose of this study was to analyze changes in mangrove forest distribution using remote sensing. The data used in this study are satellite image data from Landsat. The algorithm used is NDVI to find out the greenness of a mangrove species. Changes in the state of mangrove cover were observed in 2005-2007 and 2016-2018. Based on the analysis of mangrove cover, it was 14,723.5 ha in 2005, 13,426.5 ha in 2006, and 14,629 ha in 2007. In 2016, the mangrove cover was 23,079 ha, in 2017 it was 23,990.3 ha, and in 2018 it was 21,594.6 ha, respectively. From 2016 to 2017, there was an increase in the distribution of mangrove area by 911.3 ha. However, in 2018, the distribution of mangroves decreased by 2,395.7 ha due to land conversion. Keywords: Landsat; Mangrove; NDVI; Pangandaran